KONSEP PENDIDIKAN BERBASIS PROSES DALAM AL-QUR’AN: ANALISIS SURAH AL-GHÂSYIYAH 17–20 DAN AL-MU’MINUN 12–16 - Aliahh, Nur; Rosmiati Ramli; Sudirmanto; Siti Rondhiyah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the process-based educational concept in the Qur’an through an examination of Surah Al-Ghâsyiyah verses 17–20 and Surah Al-Mu’minun verses 12–16 to formulate Qur’anic pedagogical principles relevant to modern education. The research employs a qualitative approach using thematic exegesis and pedagogical analysis of the verses, supported by classical tafsir literature and educational theories. The findings reveal that both sets of verses present a systematic learning structure emphasizing empirical observation, gradual processes (tadarruj), intellectual reflection, and the integration of cognitive and spiritual dimensions. Surah Al-Ghâsyiyah illustrates a learning model based on observing real-world phenomena as the foundation of knowledge formation, while Surah Al-Mu’minun portrays the stages of human creation as a paradigm of progressive and structured learning development. These findings confirm that Qur’anic educational concepts are aligned with contemporary educational theories such as constructivism, inquiry learning, and developmental learning. Therefore, the Qur’an can be understood as a conceptual source of holistic education that positions process as the core of effective and meaningful learning.